Monolithic Integration of Perovskite Photoabsorbers with IGZO Thin‐Film Transistor Backplane for Phototransistor‐Based Image Sensor. Issue 1 (17th August 2022) - Chen, Tong; Wang, Chunyun; Yang, Guoshen; Lou, Qiang; Lin, Qingping; Zhang, Shengdong; Zhou, Hang
Abstract: Monolithic integration of perovskite materials and their optoelectronic devices with well‐developed thin‐film transistor (TFT) backplane is leading to new applications in displays and image sensors. Herein, a scalable polyimide assisted patterning approach for monolithic integration of perovskite based high‐sensitive phototransistor array on indium gallium zinc oxide (IGZO) active matrix backplane is introduced. Polyimide vias are first formed by conventional photolithography process, through which uniform perovskite films of arbitrary patterns with feature size less than 20 µm are fabricated by spin‐on‐patterning method. Using this technique, patterns of quasi 2D perovskite photoabsorbing layer are precisely deposited onto the channel area of the photosensing IGZO TFT, forming high‐performance phototransistors with responsivity and detectivity reaching 835.7 A W −1 and 5.4 × 10 12 Jones, respectively. An image sensor with 8 × 8 pixels array containing both photosensing perovskite/IGZO transistors and switching IGZO transistors is demonstrated, in which the switching IGZO transistor elements on the backplane are protected by the non‐patterned region of the polyimide encapsulation layer. This whole fabrication process is compatible with TFT manufacturing process and will significantly reduce the cost needed for constructing next generation high‐resolution image sensors. Abstract : A patterning process with assistant of PI paste is developed and through it the quasi 2D perovskite films can be patterned into an arbitrary shape without damage. This convenient process can reach an accuracy of at least 20 micrometers and is applied to realize a kind of quasi‐2D PSK/IGZO phototransistor array to demonstrate the potential imaging application.